260 Localized Primary Amyloidosis of Breast. (11th January 2018) - Li, Wencheng; Bergman, Simon; Butler, Dawn; Beaty, Michael; Lee, Megan
Abstract: Amyloidosis of the breast is a very rare disease. Overall, only two major case series have been published in the literature since the time primary amyloidosis of breast was first reported in 1973. Breast amyloidosis typically appears as diffuse breast involvement in the setting of systemic amyloidosis. The most common types of amyloidosis are immunoglobulin light chain amyloidosis (AL) secondary to plasma cell neoplasms, and reactive amyloidosis associated with chronic inflammation. During screening mammography, a 74-year-old woman with history of discoid lupus erythematosus was found to have an irregular mass with focal asymmetry in the medial central left breast, suspicious for breast carcinoma. Breast core biopsy showed perivascular and periductular amorphous protein deposition, positive for Congo red staining and exhibiting yellow-green birefringence under polarizing microscopy. A lymphoplasmacytic infiltrate was identified within the breast forming aggregate. The infiltrate was composed of CD20-positive B-cells and CD138-positive plasma cells, and was monoclonal for lambda light chain by in situ hybridization. The morphology and immunophenotype of the infiltrate raised the possibility of marginal zone lymphoma of breast in a setting of autoimmune disease as reported by others. The amyloidosis typing by mass spectrometry-based proteomics showed AL-lambda. Cross-sectional imaging of the chest, abdomen, and pelvis, echocardiography, serum immune electrophoresis, and bone marrow biopsy revealed no evidence of systemic amyloidosis or other immunosecretory disorder. In summary, we report a rare case of localized primary amyloidosis of the breast in the absence of systemic involvement.